Unlocking opportunities for planet-friendly school meals - Gelli, Aulo; Ruel, Marie T. (International Food Policy Research Institute, 2023)
Evidence suggests a strong link between the quality of school meals, children’s health, and both nutrition and education outcomes. School meal programs also have broad food system impacts, and thus are increasingly being designed to include objectives related to smallholder agriculture and environmental sustainability—a topic explored in a new White Paper from the School Meals Coalition on Unlocking Opportunities of Planet-Friendly School Meals, presented at the COP28 Climate Conference in Dubai on December 8.